THE DIFFERENCE IN EFFECTIVENESS BETWEEN DEMONSTRATION AND STORYTELLING METHODS OF HANDWASHING KNOWLEDGE OF FIRST- GRADERS ELEMENTARY SCHOOL CHILDREN - Lestiawati, Endang; Hapsari, Riris Puri; Retnaningsih, Listyana Natalia (Universitas Kusuma Husada Surakarta, 2025)
Background: School-age children are vulnerable to infectious diseases that can potentially lead to death. Proper handwashing is one of the effective measures for prevention. Preventive actions become more effective when health education is delivered using demonstration and storytelling methods. This study aimed to determine the effectiveness of health education using demonstration and storytelling methods on the level of handwashing knowledge among first-grade elementary school students in Krogowanan Village, Sawangan, Magelang. Methods: The research was a quasi-experimental study using a pre-test and post-test design without a control group. A total sampling technique was employed, involving 42 respondents who were divided into two groups based on the method used: demonstration and storytelling. A questionnaire was used as the research instrument. Data were analysed using the Paired T-Test and the Independent T-Test.Results: The results of the Independent T-Test revealed a statistically significant difference (p = 0.000 < 0.05) in handwashing knowledge between the groups that received demonstration and storytelling interventions. The mean increase was higher in the storytelling group (2.1429) than in the demonstration group (1.8571).Conclusions: It indicates that the storytelling method was more effective in improving handwashing skills in first-grade elementary school children.